What it looks like to ‘mind the gaps’ in a Midwest survivorship clinic for childhood cancer survivors - Stijn Hentzen; Taylor Adams; Kyla Alsman; Carolyn R. Bates; Becky Lowry (Health Care Transitions, 2023)
Background: As cancer prevalence increases and treatment improves, the population of childhood cancer survivors (CCS) will see remarkable growth. This population requires guideline-based survivorship care into adulthood; however, numerous gaps in care are common including record documentation, medical knowledge, and access to healthcare. Here we describe the patients seen in a US Midwest survivorship transition clinic (STC) and the aspects of the clinic designed to address the gaps in care this cohort faces. Methods: After IRB approval, a retrospective chart review was completed for patients established in the STC between 2014 and 2022. Results: A total of 261 patients were identified. The patients had an average age of 12 years at the time of cancer diagnosis and an average age of 28 years at clinic establishment. Patients presented from 9 states and 139 zip codes. We identified 42 different primary cancers with acute lymphoblastic leukemia (24.5%) and Hodgkin’s Lymphoma (19.2%) most common. We found that 244 (93.5%) received chemotherapy, 138 (52.9%) received radiation, and 41 (15.7%) underwent bone marrow transplant. Secondary malignancies were diagnosed in 29 (11.1%) patients with breast (23.3%) and thyroid (23.3%) malignancies most common. Discussion: The clinical diversity, complex treatment history, and prevalence of secondary malignancies in this CCS population emphasizes the importance close follow-up and adherence to survivorship guidelines. Through strong local partnerships and a specialized nursing navigator this STC addresses care gaps common in this population. Although limitations persist, STCs are a strong model of care to address the unique care needs of this growing population of complex patients.